Rendimiento académico en función del nivel de ansiedad-rasgo, sexo y habilidad general - Bauermeister, Jose J.; Colon Berlingeri, Nestor (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This study examined the relationship among trait anxiety (A-trait), sex, general ability and academic achievement of tenth-grade students in a public school in Puerto Rico. GPA was used as the criterion of academic achievement. The sample used was 144 female and 122 male subjects between 15 and 17 years old. It was found that low A-trait subjects had higher academic achievement scores than did high A-trait subjects. The female subjects had higher academic achievement scores than the male subjects. Furthermore, it was found that the academic achievement of subjects with relatively high general ability was superior to that of subjects with relatively low general ability. The results of this study were compared with those of other studies from a methodological viewpoint and in relation to the theory of state and trait anxiety advanced by Spielberger (1966a; 1970).